Multilingual Policies and Practices in Higher Education: A Nation-Wide Exploration in Colombia - Miranda, Norbella; Bonilla-Medina, Sandra Ximena; Usma Wilches, Jaime A.; Encarnación, Carmelina; Silva-Londoño, Ederson; Martínez Bula, Ligia (Íkala, Revista de Lenguaje y Cultura, 2024)
In the last two decades, foreign language policies in Colombia have prioritized English across the education system, aiming for international competitiveness and educational quality. These policies have sparked concerns among educators, including language stratification, commodification of English for the privileged, adoption of foreign benchmarks, insufficient policy implementation, and limitations of the English-Spanish bilingual model compared to multilingual perspectives. Inspired by critical race theory and decoloniality, this qualitative study examines higher education policies in Colombia, focusing on how they address multilingualism and the country’s sociocultural diversity. The study explores language policies related to student access, retention, and graduation; language requirements for faculty; and the promotion of various languages. Data collection involved a documentary analysis, interviews and surveys conducted across 16 universities from different regions of the country. Findings suggest the ongoing pervasiveness of English language-centered ideologies in most participating institutions, the invisibilities these ideologies and associated practices bring about in universities, and some emergent policies aiming at promoting multilingualism. The recommendations emanated from this study could resonate with universities both in Colombia and internationally, particularly those in similar contexts.